Segmentation of dental X-ray in endodontic treatment - Perepelytsia, O. M. (Biophysical Bulletin, 2021)
Background: The basis of successful endodontic treatment is the correct determination of the working length of the root canal (the distance between the external landmark on the crown of the tooth to the apical border). An apical constriction zone is recommended as a border for root canal treatment and filling. Intraoral radiograph allows you to obtain information about the direction of bending of the root canals, as well as to determine the working length. However, the radiograph is a two-dimensional total image and does not reproduce the entire anatomy of the apical part of the root therefore there are often layers and distortions of the image. When interpreting radiographs, there is a probability of error associated with the subjectivity of the evaluation result of the specialist. Thus, it is impractical to be guided exclusively by this method of determining the working length. The method of apexlocation is based on the difference of electrical resistance of tissues. The hard tissues of the tooth have a higher resistance than the mucous membrane of the mouth and periodontal tissue. Devices for electrometric determination of the working length of the root canal determine the impedance using alternating currents of different frequencies and apply the method of ratio. This measurement is stable and accurate even when working in wet channels and provides smooth visualization of all process of penetration of a top of the channel tool and high accuracy of definition of a place of physiological top of a root (over 80%). Modern algorithms for electrometric determination of the working length of the root canal do not combine the data obtained from the radiograph. In this regard, it is important to develop new methods and means of displaying electrometric data on the radiograph to more accurately determine the location of the physiological apex of the root. Objectives: Development of a method of segmentation of the dental radiograph to determine the area of apical narrowing. Materials and methods: principles of endodontic tooth preparation; methods for determining the working length of the root canal (radiological, electrometric); threshold segmentation method; method of segmentation of bone structures on tomographic images. Results: As a result of the performed work, the structures of the root canals of the tooth were segmented and their length was determined. Comparison of electronic determination of working length with radiological led to the fact that in some cases, X-ray and electronic length do not match. With lateral curvature of the canal, the X-ray may show a shorter working length than apexlocation devices, so the electronic working length is usually more accurate than the length determined by X-ray. Conclusions: The advantage of measuring the length of the root canal with an apex locator is much greater accuracy (about 0.5 mm) compared to the method of radiography, but the combination of these two methods is more reliable, which requires further statistical studies. Particular attention should be to the peculiarities of processing and segmentation methodsof the obtained diagnostic images to ensure the maximum quality of visualization of the contours of the root canals.